2017
DOI: 10.1016/j.clim.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged immunomodulation in inflammatory arthritis using the selective Kv1.3 channel blocker HsTX1[R14A] and its PEGylated analog

Abstract: Effector memory T lymphocytes (TEM cells) that lack expression of CCR7 are major drivers of inflammation in a number of autoimmune diseases, including multiple sclerosis and rheumatoid arthritis. The Kv1.3 potassium channel is a key regulator of CCR7− TEM cell activation. Blocking Kv1.3 inhibits TEM cell activation and attenuates inflammation in autoimmunity, and as such, Kv1.3 has emerged as a promising target for the treatment of TEM cell-mediated autoimmune diseases. The scorpion venom-derived peptide HsTX1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 74 publications
1
44
0
Order By: Relevance
“…Kv1.3 in T lymphocytes is responsible for controlling the membrane potential which is critical for the activation of these immune cells (Veytia-Bucheli et al, 2018). Several studies have confirmed that Kv1.3 is highly expressed in macrophages, microglia, and TEM cells, suggesting that Kv1.3 plays a crucial role in immune and inflammatory responses to human diseases such as multiple sclerosis (MS), rheumatoid arthritis, Type 1 diabetes, and asthma (Toldi et al, 2010;Huang et al, 2017;Tanner et al, 2017;Zhou et al, 2018). In these conditions, the expression of Kv1.3 channels is significantly elevated (Rangaraju et al, 2009), which is beneficial to define the role of Kv1.3 in autoimmune diseases as well as to clarify the significance of developing Kv1.3 blocker drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Kv1.3 in T lymphocytes is responsible for controlling the membrane potential which is critical for the activation of these immune cells (Veytia-Bucheli et al, 2018). Several studies have confirmed that Kv1.3 is highly expressed in macrophages, microglia, and TEM cells, suggesting that Kv1.3 plays a crucial role in immune and inflammatory responses to human diseases such as multiple sclerosis (MS), rheumatoid arthritis, Type 1 diabetes, and asthma (Toldi et al, 2010;Huang et al, 2017;Tanner et al, 2017;Zhou et al, 2018). In these conditions, the expression of Kv1.3 channels is significantly elevated (Rangaraju et al, 2009), which is beneficial to define the role of Kv1.3 in autoimmune diseases as well as to clarify the significance of developing Kv1.3 blocker drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Effector memory T (T EM ) cells are the subset generally associated with autoimmune- and other chronic inflammatory diseases [24-31]. Specifically in RA, T EM cells have been reported to be increased in the synovial fluid [32] and recently an inhibitor of the Kv1.3 channel (HsTX1[R14A]) was reported to reduce inflammation in the pristine-induced arthritis model by inhibiting T EM cell activation [33]. Central memory T cells (T CM ) cells do not migrate to inflamed tissues and have little to no effector function, but proliferate and differentiate to effector cells in response to antigenic stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][55] [28] A scorpion toxin inhibitor of KV1.3 was also effective in this model. [70] In both these studies, blockade of Kv1.3 alone was sufficient to ameliorate disease and simultaneous blockade of KCa3.1 was not necessary as has been suggested. [49] [71]…”
Section: Experimental Autoimmune Encephalomyelitis (Eae) a Model Formentioning
confidence: 95%